The perception of word primary stress by European Portuguese speakers - Castelo, Adelina (2022)
This paper examines the role of lexical, morphological and phonological cues in the perception of word primary stress by European Portuguese native speakers. It is based on the results of an experiment which investigates five variables: marked and unmarked stress patterns; suffixes with and without lexically marked stress; number of syllables available for echo stresses; secondary stress in compounds; and vowel reduction. The results confirm the importance of the three kinds of cues for the identification of word primary stress in this language. Although most stresses are correctly identified, subjects may become unable to locate stressed syllables when the three types of cues in a word point in different directions. In those cases, speakers tend to identify stress by primarily taking into consideration lexical information or the phonological cue of vowel reduction.